Efficacy and Safety of Tirofiban in Clinical Patients With Acute Ischemic Stroke - Han, Bin; Ma, Teng; Liu, Zhendong; Wu, Yiqun; Tan, Weiwei; Sun, Shaoyang; Li, Xuemei; Shao, Changyan; Tang, Duyong; Sun, Jinping (Frontiers in Neurology, 2022)
Background: Intravenous thrombolysis and endovascular thrombectomy have been approved for acute ischemic stroke (AIS). However, only a minority of patients received these treatments in China. We aimed to evaluate the efficacy and safety of tirofiban in AIS patients who were not undergoing early recanalization treatments. Methods: Patients with mild-to-moderate stroke (National Institutes of Health Stroke Scale (NIHSS) score, 4 -15) were enrolled in the study. Patients due to cardiogenic embolism were excluded. Eligible Patients within 12 hours from symptom onset were randomly assigned (1:1) to receive tirofiban (a loading dose of 0.4μg/kg/min over 30 minutes and a maintenance dose of 0.1μg/kg/min up to 48 hours) followed by regular treatment or to receive regular treatment (aspirin at a dose of 100 mg per day for 90 days) (control). The primary outcome was the proportion of favorable functional outcome at 90 days (defined as a modified Rankin Scale (mRS) score of 0-2). The secondary outcomes included a shift in the distribution of mRS scores at 90 days, the NIHSS score at 24 hours and at 7 days. The primary safety outcome was symptomatic intracranial hemorrhage (sICH) within 7 days after tirofiban treatment. Results: A total of 380 eligible patients were randomly assigned to the tirofiban group (n=190) or the control group (n=190). The proportion of favorable functional outcomes was higher in the tirofiban group (79.1%) than that in the control group (67.8%) at 90 days (odds ratio [OR], 1.80; 95% CI, 1.12 to 2.90; P=0.0155). An improvement was also observed in the overall distribution of the 90-day mRS scores (adjusted common OR, 2.31; 95% CI, 1.58 to 3.39; P<0.0001). Additionally, the median NIHSS score was lower in the tirofiban group than in the control group at 7 days (3 vs 5, P<0.0001). Next, we observed that the occurrence of sICH did not differ between the two groups. Conclusions: Our trial supports that tirofiban was safe and effective and might be a remedial treatment for AIS patients who did not receive recanalization treatments. Clinical trial registration: URL: http://www.chictr.org.cn/. Unique identifier: ChiCTR2000031297.